Relationship between Temperature and Humidity with Tuberculosis Incidence in the Community - Ikhtiar, Muhammad; Sididi, Mansur (GLOBAL HEALTH SCIENCE GROUP, 2024)
The global commitment to ending tuberculosis is outlined in the End TB Strategy, which targets an 80% reduction in tuberculosis incidence and 90% reduction in tuberculosis deaths by 2030. Objective: found a relationship between temperature and humidity with pulmonary TB. This research is a quantitative research with a cross sectional study approach. Independent and dependent variables are measured simultaneously at the same time. The sampling method used is simple random sampling with a sample size of 138 Data analysis using the Chi Squaretest. The results of the chi square test obtained a value of p = 0.001 < 0.05, meaning that there is a relationship between temperature and humidity with the incidence of tuberculosis. Based on the results of the study, it was found that there were 73 respondent houses (52.9%) whose house temperatures met the requirements and 65 respondents (47.1%) who did not meet the requirements, meaning that there was a relationship between temperature and the incidence of tuberculosis. The results of the chi square test p = 0.001 < 0.05, which means that there is a significant relationship between temperature and the incidence of tuberculosis with a 4.66 times greater risk of getting TB. There is a relationship between temperature and humidity with the incidence of tuberculosis in Salo sub-district.